2014
DOI: 10.5812/iranjradiol.4242
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Ankylosing Spondylitis and Hereditary Multiple Exostoses:Coincidence or Association

Abstract: Coexisting ankylosing spondylitis and hereditary multiple exostoses have rarely been reported (three patients) previously. A 27-year-old man with hereditary multiple exostoses is presented as a fourth report. At the age of 15 years, the patient had multiple exostoses around the knee, ankle and shoulder joints. He was diagnosed with ankylosing spondylitis 3 years ago. The patient’s sister and his 3 brothers also have multiple exostoses without any family history of spondyloarthropathy or inflammatory arthritis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is hypothesized that loss of function of EXT1 or EXT2 in subjects with HME can affects pancreatic insulin secretion capacity and development (46). With only four cases of coexistence of HME and ankylosing spondylitis so far, it seems that either association of HME and ankylosing spondylitis could be a rare entity or a coincidence (47). The increase in the number of reported patients who have a coexistence of these two diseases might suggest that this association is stron- ger than a coincidence.…”
Section: Associate Disordersmentioning
confidence: 97%
“…It is hypothesized that loss of function of EXT1 or EXT2 in subjects with HME can affects pancreatic insulin secretion capacity and development (46). With only four cases of coexistence of HME and ankylosing spondylitis so far, it seems that either association of HME and ankylosing spondylitis could be a rare entity or a coincidence (47). The increase in the number of reported patients who have a coexistence of these two diseases might suggest that this association is stron- ger than a coincidence.…”
Section: Associate Disordersmentioning
confidence: 97%
“…Other manifestations described in individuals with HME, which could be rare features of the disease, include abnormal scarring and poor wound healing (Hosalkar et al, 2007), ankylosing spondylitis reported in four individuals (Rostamian et al, 2014), and autism and intellectual disability reported in two unrelated individuals (Li et al, 2002). However, none of the reported patients with these features underwent a comprehensive genetic diagnostic evaluation to rule out the coincidental association of a second genetic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Limited bone involvement differentiates HME from other syndromes. However, few studies have reported the coexistence of HME with other non‐bone‐related features, such as poor wound healing, ankylosing spondylitis, learning disabilities, and autism (Hosalkar et al, 2007; Li et al, 2002; Rostamian et al, 2014). Here, we present two unrelated probands with typical radiological features of HME and pathogenic variants in EXT1 as well as vascular malformation, a clinical feature not previously described in individuals with HME.…”
Section: Introductionmentioning
confidence: 99%